Do Insiders Earn More in Stock Markets? An Experiment - Qureshi, Muhammad Azeem (Economic Journal of Nepal, 2011)
Academicians as well as practitioners have long been debating insider information. Controlled laboratory• experiment may be one way to estimate possible gains of an insider vis-a-vis a common investor given certain level of market efficiency. This paper reports the results of such a laboratory experiment using System Dynamics method; carried out to see effects of insider information on the profitability of the insiders versus that of the uniformed common investors. This study confirms that in a market, which has the ability to reflect the company inside information in market prices in one day, insiders cannot outperform the un-informed investors. However, another study with participant having investment knowledge or the practitioners from the stock markets may be carried out to know whether such a knowledge or expertise makes a difference. Another study could be carried out for those markets that could reflect inside information with a larger time lag. Key words: Stock markets; Reflect the company; Pakistan Economic Journal of Nepal A Quarterly Publication of the Central Department of Economics T.U., Kirtipur Vol. 31, No. 4 October-December 2008, Issue No. 124 Page: 235-245 Uploaded date: 5 July 2011